Competencias del orientador de centros subvencionados vulnerables para la mejora de la convivencia escolar: Competencies of the counselor of subsidized vulnerability centers for the improvement of school life - Daniel Villarroel Montaner, Joaquín Gairín Sallàn, José Garcés Bustamante , (Revista de Orientación Educacional, 2019)
Este estudio levanta un perfil de competencias del orientador escolar en centros educativos subvencionados en contextos vulnerables, en base a las interrogantes: ¿Hay un perfil de competencias para el orientador del subsistema particular subvencionado chileno vulnerable? Cuando un representante legal contrata a este profesional, ¿con qué tipo de perfil se guía? Se trata de una investigación cualitativa con una metodología de datos mixta mediante un diseño etnográfico, analizándose 3 documentos oficiales, 1 focus group con registro multimedia, 3 cuestionarios y 5 reuniones del Comité de Orientación Escolar, contando con la participación de directivos, orientadores y expertos. Los resultados arrojaron cuatro dominios de intervención: Liderazgo orientador, Gestión de proyectos de orientación, Orientación vocacional y el desarrollo personal y Acompañamiento pedagógico con dieciséis competencias profesionales. Abstract: This study is about creating a skill profile of the school counselor of vulnerable subsidized schools, according to the following questions: Is there a skill profile for the school counselor of vulnerable schools of the subsidized subsystem in Chile? When a legal representative hires this profesional, what type of profile is based on? It is an investigation based on a qualitative study using a mixed methodology and ethnographic design, analyzing 3 official documents and 1 focus group with multimedia records, 3 questionnaires and 5 meetings of four Committee on School Counselor, with the participation of school managers, school counselors and experts in the field. The results of the research produced four domains: counselor leadership, guidance management projects, vocational guidance and personal development and pedagogical accompaniment with sixteen professional skills.